A 70-kd protein of the yeast mitochondrial outer membrane is targeted and anchored via its extreme amino terminus. - Hase, T (1984)
The major 70-kd protein of the yeast mitochondrial outer membrane is made on cytosolic ribosomes and imported into the outer membrane without proteolytic cleavage. We have attempted to identify the sequences which target the protein to the mitochondria and which permanently anchor it to the lipid bilayer of the outer membrane. By manipulating the cloned gene we have deleted 13 different regions throughout the polypeptide; in addition, we have fused amino-terminal regions of different length to beta-galactosidase. Each altered gene was introduced into yeast and the intracellular fate of the corresponding polypeptide product was determined by subcellular fractionation. All the information for targeting and anchoring the 70-kd protein (617 amino acids) was contained within the amino-terminal 41 amino acids. When this entire region was deleted, the protein was recovered with the cytosol fraction. However, several restricted deletions within this amino-terminal region appeared to affect targeting and anchoring differentially: most of the altered protein remained in the cytosol but a small fraction was misrouted into the mitochondrial matrix space. We suggest that targeting is mediated by a region which includes the 11 amino-terminal amino acids whereas the permanent membrane anchor is provided by a typical transmembrane sequence between residues 9 and 38.